Angular Versus Curved Shapes: Correspondences and Emotional Processing. (January 2018) - Blazhenkova, Olesya; Kumar, Melisa Maya
The present work aimed to systematically examine sensory and higher level correspondences to angular and curved shapes. Participants matched angular and curved abstract shapes to sensory experiences in five different modalities as well as to emotion, gender, and name attributes presented as written labels (Study 1) and real experiences (Study 2). The results demonstrated nonarbitrary mapping of angular and curved shapes to attributes from all basic sensory modalities (vision, audition, gustation, olfaction, and tactation) and higher level attributes (emotion, gender, and name). Participants associated curved shapes with sweet taste, quiet or calm sound, vanilla smell, green color, smooth texture, relieved emotion, female gender, and wide-vowel names. In contrast, they associated angular shapes with sour taste, loud or dynamic sound, spicy or citrus smell, red color, rough texture, excited or surprise emotion, male gender, and narrow-vowel names. These prevalent correspondences were robust across different shape pairs as well as all sensory and higher level attributes, presented as both verbal labels and real sensory experiences. The second goal of this research was to examine the relationship between the shape correspondences and individual differences in emotional processing, assessed by self-report and performance measures. The results suggest that heightened emotional ability is associated with making shape attributions that go along with the found prevalent trends.